2016
DOI: 10.1007/s11418-015-0959-8
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive cyclolanstane-type saponins from the stems of Astragalus membranaceus (Fisch.) Bge. var. mongholicus (Bge.) Hsiao

Abstract: Twelve cyclolanstane-type saponins including six new ones, astrolanosaponins A1 (1), A2 (2), B (3), C (4), D (5), and E (6) were obtained from the stem of Astragalus membranaceus (Fisch.) Bge. var. mongholicus (Bge.) Hsiao, and their structures were elucidated by chemical and spectroscopic methods. Of the known ones, cycloastragenol-3-O-β-D-glucopyranoside (7), astraverrucin II (8), cycloaraloside E (9), huangqiyenin A (10), and huangqiyenin B (11) were isolated from the species first. Meanwhile, compounds 1-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…The previous research indicated that polysaccharides, triterpenoids, and isoflavonoids were the major constituents of A. membranaceus var. mongholicus roots, and these triterpenoids consisted of cycloartane and oleanane types. ,, Malabaricane triterpenoids were isolated from the genus Astragalus for the first time in the present investigation, and the discovery of 1 – 20 revealed a new kind of chemical constituents in the species studied. Considering the traditional effects and biological activities of its roots, the migratory inhibitory activity using HepG2 cells and the antiproliferative activity against six human cancer cell lines (SW480, MCF-7, SH-SY5Y, HELa, PANC-1, and HepG2) of 1 – 20 were evaluated.…”
mentioning
confidence: 62%
“…The previous research indicated that polysaccharides, triterpenoids, and isoflavonoids were the major constituents of A. membranaceus var. mongholicus roots, and these triterpenoids consisted of cycloartane and oleanane types. ,, Malabaricane triterpenoids were isolated from the genus Astragalus for the first time in the present investigation, and the discovery of 1 – 20 revealed a new kind of chemical constituents in the species studied. Considering the traditional effects and biological activities of its roots, the migratory inhibitory activity using HepG2 cells and the antiproliferative activity against six human cancer cell lines (SW480, MCF-7, SH-SY5Y, HELa, PANC-1, and HepG2) of 1 – 20 were evaluated.…”
mentioning
confidence: 62%
“…Between 1983 and 2020, 189 small molecules have been isolated from AM and AMM, including 77 triterpenoid saponins and sapogenins ( 1 – 77 ), 88 flavonoids and their glycosides ( 78 – 165 ), and 24 other compounds ( 166 – 189 ) (Tables 1–3, Figures 1–8). 19–76 …”
Section: Chemical Constituents Of Am and Ammmentioning
confidence: 99%
“…plants can provide abundant drug screening entities with high-molecular diversity (16). our previous studies examined the separation and identification of natural products from traditional chinese herbs (17)(18)(19)(20). Based on our previous studies, a natural product library containing 1,235 compounds derived from traditional chinese herbs with anti-metabolic effect was developed.…”
Section: Discovery Of Natural Adenosine Monophosphate-activated Prote...mentioning
confidence: 99%
“…The compounds selected for virtual screening were separated and purified from traditional Chinese herbs that have anti-metabolic effects, according to our previous study. all the structures were determined by nuclear magnetic resonance spectrometry, infrared spectrum, and mass spectrometry (17)(18)(19)(20).…”
Section: Discovery Of Natural Adenosine Monophosphate-activated Prote...mentioning
confidence: 99%